Error Patterns in Algebraic Equation in Secondary Mathematics Education (Voice: A Biannual & Bilingual Journal, 2025)
This study investigates pattern of error in algebraic equation solving that occurs among Grade IX students. This study used Newman's Error Analysis Framework to investigate the errors. This study consist of 34 incorrect response sheets from a secondary school in Kathmandu, Nepal, as sampling frame and four representative cases were examined to identify particular misconceptions in solving algebraic equations. This study mainly concentrate on a two-digit number related word problem necessary for students to formulate linear equations and solve for unknown variables. The findings explore the systematic errors across different cognitive levels. The comprehension errors in the interpretation of digit reversal conditions, transformation errors related to converting verbal statements to mathematical equations, process skill errors was based on algebraic manipulations, and encoding errors is related to the finding of final solutions. The most serious challenge appears during the transformation stage, where students failed to properly translate the problems into correct mathematical forms. These determined misconceptions suggest the demand of targeted instructional strategies that address conceptual understanding rather than procedural memorization, emphasizing the significance of conceptual change theory in mathematics education.